A Fad too Far? Dietary Strategies for the Prevention and Treatment of NAFLD. Issue 10 (6th September 2020) - Moore, Mary P.; Cunningham, Rory P.; Dashek, Ryan J.; Mucinski, Justine M.; Rector, R. Scott
Abstract : Nonalcoholic fatty liver disease (NAFLD) is a major health problem, and its prevalence has increased in recent years, concurrent with rising rates of obesity and other metabolic diseases. Currently, there are no FDA‐approved pharmacological therapies for NAFLD, and lifestyle interventions, including weight loss and exercise, remain the cornerstones for treatment. Manipulating diet composition and eating patterns may be a sustainable approach to NAFLD treatment. Dietary strategies including Paleolithic, ketogenic, Mediterranean, high‐protein, plant‐based, low‐carbohydrate, and intermittent fasting diets have become increasingly popular because of their purported benefits on metabolic disease. This review highlights what is currently known about these popular dietary approaches in the management of NAFLD in clinical populations with mechanistic insight from animal studies. It also identifies key knowledge gaps to better inform future preclinical and clinical studies aimed at the treatment of NAFLD.